ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA PADA MATA KULIAH MICRO TEACHING: (STUDI PADA MAHASISWA ANGKATAN 2018 DI PROGRAM STUDI PENDIDIKAN EKONOMI) - Marlon Ryanto Chera; Amjad Salong; Silvia Manuhutu (P3M Politeknik Negeri Ambon, 2022)
This study aims to determine teaching skills through micro teaching courses in 2018 students of the Economic Education Study Program FKIP UNPATTI. This type of research is a qualitative research using a phenomenological approach. The informants in this study were lecturers of the micro teaching subject in the Economic Education Study Program with a total of 2 people. The data collection technique used is interviews. While the data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. The results showed that the teaching skills of the 2018 Economics Education Study Program students in carrying out the basic skills of teaching students had implemented the five basic teaching skills, but they were still not implemented perfectly based on the components of each skill, namely opening and closing lessons and skills providing reinforcement. where some students do not provide motivation and just stand in front of the class without any gestures that show warmth. Keywords: Basic Teaching Skills, Micro Teaching..